Quantifying Training and Game Demands of a National Basketball Association Season - Russell, Jennifer L.; McLean, Blake D.; Stolp, Sean; Strack, Donnie; Coutts, Aaron J. (Frontiers in Psychology, 2021)
Purpose: There is currently no data describing combined practice and game load demands throughout a National Basketball Association (NBA) season. The primary objective of this study was to integrate external load data garnered from all on-court activity throughout an NBA season, according to different activity and player characteristics. Methods: Data from 14 professional male basketball players (meanSD; age, 27.34.8 years; height, 201.07.2 cm; body mass, 104.910.6 kg) playing for the same club during the 2017-2018 NBA season was retrospectively analyzed. Game and training data were integrated to create a consolidated external load measure, which was termed integrated load. Players were categorized by years of NBA experience (1-2y, 3-5y, 6-9y and 10+y), position (frontcourt and backcourt), and playing rotation status (starter, rotation, bench). Results: Total weekly duration was significantly different (p < 0.001) between years of NBA playing experience, with duration highest in 3-5 year players, compared with 6-9 (d=0.46) and 10+ (d=0.78) year players. Starters experienced the highest integrated load, compared with bench (d=0.77) players. There were no significant differences in integrated load or duration between positions. Conclusions: This is the first study to describe the seasonal training loads of NBA players for an entire season, and shows that a most training load is accumulated in non-game activities. This study highlights the need for integrated and unobtrusive training load monitoring, with engagement of all stakeholders to develop well-informed individualized training prescription to optimize preparation of NBA players.